2014
DOI: 10.1097/meg.0000000000000076
|View full text |Cite
|
Sign up to set email alerts
|

Treatment for chronic hepatitis C in a cohort of opiate substitution therapy recipients in three Swedish cities – completion rates and efficacy

Abstract: Despite the low HRQoL and the high occurrence of depression, HCV treatment was feasible and showed satisfactory rates of completion in this cohort of unselected OST recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 15 publications
2
13
1
Order By: Relevance
“…Improved medical management and better patient compliance with treatments for chronic disease whilst in OST may explain these associations. This hypothesis is supported by evidence that people in OST comply with HCV treatment and can achieve sustained virological response (Jerkeman et al, 2014;Sasadeusz et al, 2011). They have also been shown to commence HIV anti-retroviral therapy (ART) more rapidly than those out of OST and also have higher rates of ART adherence (Metzger et al, 2010).…”
Section: Discussionmentioning
confidence: 95%
“…Improved medical management and better patient compliance with treatments for chronic disease whilst in OST may explain these associations. This hypothesis is supported by evidence that people in OST comply with HCV treatment and can achieve sustained virological response (Jerkeman et al, 2014;Sasadeusz et al, 2011). They have also been shown to commence HIV anti-retroviral therapy (ART) more rapidly than those out of OST and also have higher rates of ART adherence (Metzger et al, 2010).…”
Section: Discussionmentioning
confidence: 95%
“…Such studies are usually associated with higher treatment uptake and demonstrate feasibility of treatment, even in people who are currently injecting drugs [5,6,26,27].…”
Section: Discussionmentioning
confidence: 98%
“…In recent work completed within the Veteran's Administration hospital system, investigators have developed a population based clinical and comprehensive programme led by pharmacists which led to an increase in appropriate testing, treatment and an increase in adherence resulting in an increase in SVR achievement . In the hard to treat populations including patients with HIV, cirrhosis, psychiatric disorders, and use of intravenous drugs, studies have reported successful treatment when patients were monitored closely, received personalised treatment, and had their pre‐existing conditions such as depression addressed prior to the initiation of treatment and vigorously treating treatment side effects …”
Section: The Role Of Treatment Regimen Adherence and Pro'smentioning
confidence: 99%
“…In fact, providing anti‐HCV treatment with lots of side effects and long duration of treatment presented a challenge to keep patients adherent to the regimen. In this instance, investigators recognised that sharing information about early virologic response at week 4, 8 or 12 helped patients stay adherent to treatment regimen …”
Section: The Role Of Treatment Regimen Adherence and Pro'smentioning
confidence: 99%
See 1 more Smart Citation